Adaptation and evaluation of the Family Involvement and Alienation Questionnaire for use in the care of older people, psychiatric care, palliative care and diabetes care. (4th May 2018) - Ewertzon, Mats; Alvariza, Anette; Winnberg, Elisabeth; Leksell, Janeth; Andershed, Birgitta; Goliath, Ida; Momeni, Pardis; Kneck, Åsa; Skott, Maria; Årestedt, Kristofer
Abstract: Aim: To adapt the Family Involvement and Alienation Questionnaire (FIAQ) for use in the care of older people, psychiatric care, palliative care and diabetes care and to evaluate its validity and reliability. Background: Involvement in the professional care has proven to be important for family members. However, they have described feelings of alienation in relation to how they experienced the professionals' approach. To explore this issue, a broad instrument that can be used in different care contexts is needed. Design: A psychometric evaluation study, with a cross‐sectional design. Method: The content validity of the FIAQ was evaluated during 2014 by cognitive interviews with 15 family members to adults in different care contexts. Psychometric evaluation was then conducted (2015–2016). A sample of 325 family members participated, 103 of whom in a test–retest evaluation. Both parametric and non‐parametric methods were used. Results: The content validity revealed that the questionnaire was generally understood and considered to be relevant and retrievable by family members in the contexts of the care of older people, psychiatric care, palliative care and diabetes care. Furthermore, the FIAQ (Revised), demonstrated satisfactory psychometric properties in terms of data quality, homogeneity, unidimensionality (factor structure), internal consistency and test–retest reliability. Conclusion: The study provides evidence that the FIAQ (Revised) is reliable and valid for use in further research and in quality assessment in the contexts of the care of older people, psychiatric care, palliative care and diabetes care.